STAGES OF INTERNATIONAL LEGAL REGULATION IN THE FIELD OF CLIMATE PRESERVATION - Putilina, M.I. (Vestnik Brânskogo gosudarstvennogo universiteta, 2021)
The subject of the article is a chronological analysis of the development of the institutions of international law that regulate the issue of climate preservation. Active international legal cooperation in this area can be seen as a sign of growing attention of the international community to the problem of climate change, its integration into other areas of politics and law. This article provides a periodization of the stages of the process of formation of the main institutions of environmental law in the field of climate preservation from 1972 to the present, considers the most important milestones within the proposed stages, systematizes this information, gives comparative assessments of legal documents, taking into account their effectiveness at all stages as they are adopted. The study revealed the continuity of the process of adapting the adopted agreements to changing perceptions about set goals, quantitative assessments of the fulfillment of their obligations by states, the effectiveness of institutions for the implementation of agreements both at the international and regional or national levels. The author concludes that the United Nations Framework Convention on Climate Change (UNFCCC), the Kyoto Protocol and the Paris Agreement have played a key role in stimulating and guiding international legal efforts to preserve the climate.